Unpacking Australia’s “China Threat” Discourse: A Constructivist Approach - De Silva, Shakthi (Taylor and Francis, 2025)
While most scholarship on great power contestations relies on a Realist framework that focuses on military and economic power and treats states as rational actors seeking to maximise gains in an anarchic international system, Constructivist theory offers a different perspective. Constructivist contributions to international relations theory show how material variables—such as military and economic power—acquire meaning only within a social context, as they interact with historical legacies, cultural norms, and other ideational factors. An understanding of how material variables interact with ideational variables to determine states’ interests can yield better insights into how threat perceptions take form. Adopting a constructivist approach, this chapter sheds light on Australia’s threat perceptions of China through a discourse analysis of various primary sources such as speeches of Australian policymakers, Government White Papers, and public opinion polls, from the period between 2003 and 2023. The chapter uncovers a heightened threat perception of China—particularly from 2016 onwards—stemming from Australia’s view of China’s behaviour in the South China and East China Seas, its attitude towards international norms, its engagement in the Pacific, and its recent violations of multilateral trade rules and coercive economic measures imposed on Australia. The chapter concludes with several policy recommendations for Canberra: while Australia may benefit from its membership in the Quad and AUKUS in the long run, it is imperative to preserve its ongoing political and economic relationship with China. Achieving this requires Australia to engage in a delicate tightrope balance.
Keywords: Australia; China; Constructivism; Foreign Policy; Threat perception